2019
DOI: 10.1136/bcr-2019-230877
|View full text |Cite
|
Sign up to set email alerts
|

Left renal vein entrapment syndrome: nutcracker syndrome!

Abstract: Nutcracker syndrome (NCS) is a rare vascular compression disorder that involves compression of the left renal vein most commonly between the aorta and the superior mesenteric artery (SMA), although variations exist. It is associated with the formation of the left renal vein from the aortic collar during the 6th–8th week of gestation and abnormal angulation of the SMA from the aorta. Collateralisation of venous circulation including mainly the left gonadal vein and the communicating lumbar vein are the most sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…NCS could be differentiated clinically into two subtypes as follows: renal presentations and non-renal presentations [ 2 ]. Hematuria, orthostatic proteinuria with or without flank pain is the common renal clinical presentations [ 3 ]. The non-renal presentations include abdominal pain, varicocele, dyspareunia, dysmenorrhea, fatigue, and orthostatic intolerance and so on [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…NCS could be differentiated clinically into two subtypes as follows: renal presentations and non-renal presentations [ 2 ]. Hematuria, orthostatic proteinuria with or without flank pain is the common renal clinical presentations [ 3 ]. The non-renal presentations include abdominal pain, varicocele, dyspareunia, dysmenorrhea, fatigue, and orthostatic intolerance and so on [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A rarer condition is posterior nutcracker, when the LRV is compressed between the aorta and the vertebral body. The term 'nutcracker syndrome', first described by De Schepper in 1972, is preferred over phenomenon if the vascular compression becomes symptomatic 2,3 .…”
Section: Discussionmentioning
confidence: 99%
“…N utcracker syndrome (NCS) is a condition caused by compression of the left renal vein (LRV), most often, between abdominal aorta and superior mesenteric artery (SMA) 1,2 . It may cause many symptoms in both children and adults, such as intermittent hematuria, proteinuria, flank pain, pelvic congestion in females, and varicocele in male patients.…”
Section: Introductionmentioning
confidence: 99%
“…This is a rare situation whose prevalence is unknown [ 4 ]. It has been described as more common in women in the third or fourth decade, although a later study showed equal prevalence between men and women [ 5 ] with a peak prevalence in adults between 20 and 30 years old probably related to the rapid development of vertebral bodies during puberty, causing a narrowing of the angle between the abdominal aorta and the superior mesenteric artery [ 6 ] compression of the left renal artery is most often anterior, between the abdominal aorta and the superior mesenteric artery, more rarely compression is posterior when the left renal vein passes between the abdominal aorta and the spine, then we speak of a posterior nutcracker syndrome [ 7 ] the other etiologies: Pancreatic tumors, para-aortic adenopathy, retroperitoneal tumors, abdominal aortic aneurysm, duplication of the left renal vein, left renal ptosis, lordosis and decrease of retroperitoneal and mesenteric adipose tissue [ 8 ] the nutcracker syndrome can be clinically differentiated into 2 subtypes as follows: typical presentation (or renal presentation) and atypical presentation (or urological presentation). The typical clinical presentation includes hematuria, orthostatic proteinuria with or without flank pain.…”
Section: Discussionmentioning
confidence: 99%